Relationship marketing: Its potential to enhance public-private sector initiatives - Davis, Peter (2002)
In an effort to obtain value for money and eliminate waste and inefficiency, inherent within the public sector, Governments throughout the world are actively encouraging the private sector to become interested in funding public infrastructure projects. There are several examples within Australia where the Federal Government has enabled the private sector to have a financial interest in procurement of their projects [1]. Reasons for this are cited as: allocation of risk, guaranteed maximum price and importantly within the context of this paper: close integration of the process and product together with improved cost efficiency. To enable and build from these benefits an understanding of the concept of relationship marketing (RM) is required. Accordingly a review of the attributes and both positive and negative issues associated with RM follows.